Dosing in Heavy-weight/Obese Patients with the LMWH, Tinzaparin: A Pharmacodynamic Study - Hainer, James W.; Barrett, Jeffrey S.; Assaid, Christopher A.; Fossler, Michael J.; Cox, Donna S.; Leathers, Todd; Leese, Philip T. (Thrombosis and Haemostasis, 2002)
This pharmacodynamic study examined weight-based dosing of the low molecular weight heparin (LMWH), tinzaparin, in heavyweight/obese subjects. Single doses (175 and 75 IU/kg) were administered subcutaneously (SC) to 37 healthy heavy-weight subjects (101-165 kg; 26-61 kg/m2). AUA and Amax values of anti-Xa and anti-IIa activities were consistent over these body weight and body mass index (BMI) ranges, indicating that tinzaparin pharmacodynamics are not influenced by body weight or BMI. The range of AUA and Amax values in the study population overlapped that of historical control normal-weight subjects (<100 kg), indicating that weightadjusted tinzaparin dosing yields a predictable response regardless of body weight or BMI. Tinzaparin was well tolerated, although injection site bruising was commonly reported. SC tinzaparin dosing in heavy or obese patients is appropriate based on body weight alone; the dose need not be capped at a maximal absolute dose.
Keywords: Low molecular weight heparin; tinzaparin; obesity; weight-based dosing; Innohep